A2/B1 Promotes NRF2 mRNA Stability and Inhibits Ferroptosis and Cell Proliferation in Breast Cancer Cells. - Huang, Yan; Chen, Jingjing; Pan, Juan; Yang, Yifu; Huang, Hongwu; Lai, Huiping; Yang, Lei; Ai, Hongyan (BioMed Research International, 2023)
Breast cancer is a highly harmful malignant tumor, which poses a great threat to women's body and mind, and the mortality rate ranks second among all women's diseases. The incidence rate accounts for 7-10% of various malignant tumors in the whole body, second only to uterine cancer in women, and has become the main cause of threatening women's health. Advanced breast cancer is often considered an incurable disease. The family of heterogeneous nuclear ribonucleoprotein complexes is composed of about 20 hnRNP proteins with molecular weights ranging from 32 to 120 kDa, and they are named according to their molecular weights. Among them, hnRNPA2 and hnRNPB1 are the two most important members of the hnRNP family, both derived from the same gene on chromosome 7p15. Therefore, research to understand the molecular mechanism and process of breast cancer progression has an important role in promoting the current medical research on breast cancer treatment methods. Therefore, studying the mechanism of tumorigenesis is the key to tumor prevention and treatment. Therefore, this paper proposes that A2/B1 promotes the stability of NRF2 mRNA and inhibits ferroptosis and cell proliferation in breast cancer cells. The article mainly introduces the disease diagnosis method based on artificial neural network and its neural network algorithm. In the experimental part, the activity of hnRNP A2/B1 on cancer cells is deeply studied. The results show that the absorbance of the MTT method increases continuously with the extension of the culture time, and the maximum reaches 1.2. This fully shows that its absorption capacity is very strong, especially after 24 hours, the absorption rate rises from 0.6 to 0.9, which shows that 24 hours is the best absorption time. And it can also be found that hnRNPA2/B1 has a significant inhibitory effect on breast cancer cells; it can reduce the effect on breast cancer cell cycle and apoptosis.